Vì
\(\left|x-2\right|\ge0\)
\(\left(y+2x\right)^2\ge0\)
\(\left|z+y\right|\ge0\)
\(\Rightarrow\left|x-2\right|+\left(y+2x\right)^2+\left|z+y\right|\ge0\)
Dấu "=" xảy ra khi \(\hept{\begin{cases}\left|x-2\right|=0\\\left(y+2x\right)^2=0\\\left|z+x\right|=0\end{cases}}\)
=> x = 2
<=> ( y + 2.2 )2 = 0
=> y + 4 = 0
=> y = - 4
<=> |z + ( - 4 )|= 0
<=> z = 4
Vậy x = 2; y = - 4 ; z = 4
Ta có:\(\left|x-2\right|=0\Rightarrow x=2\)
Tiếp tục tìm y, thế x, ta có: \(\left(y+2.2\right)^2=0\)
\(\Rightarrow\left(y+4\right)^2=0\)
\(\Rightarrow y+4=0\)
\(\Rightarrow y=-4\)
Đã có y, ta tiếp tục tìm z: \(\left|z+-4\right|=0\)\(\Rightarrow z=4\)
Vậy \(x=2;y=-4;z=4\)